Plant elicitor Peptides regulate root hair development in Arabidopsis - Jing, Yanping; Zhao, Fugeng; Lai, Ke; Sun, Fei; Sun, Chenjie; Zou, Xingyue; Xu, Min; Fu, Aigen; Sharifi, Rouhallah; Chen, Jian; Zheng, Xiaojiang; Luan, Sheng (Frontiers in Plant Science, 2024)
Plant Elicitor Peptides (Peps) induce plant immune responses and inhibit root growth through their receptors PEPR1 and PEPR2, two receptor-like kinases. In our study, we found a previously unknown function of Peps that enhance root hair growth in a PEPRs-independent manner. When we characterized the expression patterns of PROPEP genes, we found several gene promoters of PROPEP gene family were particularly active in root hairs. Furthermore, we observed that PROPEP2 is vital for root hair development, as disruption of PROPEP2 gene led to a significant reduction in root hair density and length. We also discovered that PROPEP2 regulates root hair formation via the modulation of CPC and GL2 expression, thereby influencing the cell-fate determination of root hairs. Additionally, calcium signaling appeared to be involved in PROPEP2/Pep2-induced root hair growth. These findings shed light on the function of Peps in root hair development.